Temperate snake community in South America : is diet determined by phylogeny or ecology? - Bellini, Gisela Paola (2015)
Fil: Bellini, Gisela Paola. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Nacional de Limnología; Argentina.